Gene expression profiling in follicular lymphoma and its implication for clinical practice - Janikova, Andrea; Tichy, Boris; Supikova, Jana; Stano-Kozubik, Katerina; Pospisilova, Sarka; Kren, Leos; Vasova, Ingrid; Salek, David; Mayer, Jiri (Leukemia & lymphoma, 2011)
Follicular lymphoma (FL) is characterized by an indolent and relapsing course. Recently, the clinical outcome of FL has been distinguished by immune microenvironment-associated gene signatures. In our study, gene expression profiling (GEP) was performed in 31 non-selected patients with follicular lymphoma (FL), 12 of whom were in relapse and the remaining 19 newly diagnosed. A custom oligonucleotide microarray (Agilent 8 × 15K) was used which contained probes for about 3500 genes, including those that had been previously published as demonstrating significant prognostic value. An unsupervised approach was not able to recognize clinically different FLs. As the previously published prognostically relevant gene signatures could not be properly verified, probably due to microarray platform differences, template matching was therefore used in order to define two gene sets with differential gene expression among our samples. These gene sets shared an overrepresentation of genes with similar biological functions and were termed 'T-CELL' and 'PROLIFERATION' profiles. The 'poor profile' was then defined by a high PROLIFERATION score (upper tertile) and/or low T-CELL score (lower tertile). The 'poor profile' cohort contained a significantly higher proportion of relapsed cases (p < 0.05, Fisher's exact test). Additionally, a comparison of samples from initial diagnosis and from relapse showed significant differences mainly in the T-CELL profile (p = 0.036; χ(2)). This supports the hypothesis that the number of T-cells and their expression pattern play a major role in FL development.
Keywords: dospělí; Oligonucleotide Array Sequence Analysis; Adult; Neoplasm Recurrence, Local; RNA nádorová; lidé; Lymphoma, Follicular; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; následné studie; míra přežití; stanovení celkové genové exprese; prognóza; RNA, Messenger; Follow-Up Studies; Reverse Transcriptase Polymerase Chain Reaction; nádorové biomarkery; Aged; lokální recidiva nádoru; Prognosis; Survival Rate; RNA, Neoplasm; folikulární lymfom; lidé středního věku; Biomarkers, Tumor; senioři; Middle Aged; Gene Expression Profiling; Humans